Internalization of Phospholipid-Coated Gold Nanoparticles - Lindsay J. Shearer (Crystals, 2019)
Gold nanoparticles are used in health-related research; however, their effectiveness appears to depend on how well they are internalized and where they are destined to travel. Internalization in cells is efficient if the gold nanoparticles are biocompatible, where one possible pathway of cell entry and processing is clathrin-mediated endocytosis. In this work we studied the co-localization of phospholipid-coated gold nanoparticles (PCAuNPs) with markers of the endocytic pathway (Rab and LAMP-1 proteins) in C2C12 and A549 cells and found that the internalization was consistent with clathrin-mediated endocytosis and was cell type dependent. We further found that the time evolution of uptake and disposal of these PCAuNPs was similar for both cell types, but aggregation was more significant in A549 cells. Our results support the use of these PCAuNPs as models for potential drug delivery platforms.